"Daniel was racist": Individualizing racism when teaching about the Civil Rights Movement. (3rd July 2019) - Wills, John S.
ABSTRACT: This study investigated how racism was represented in a unit on civil rights in three 11th-grade U.S. history classes. Using qualitative methods, I observed classroom lessons in three teachers' classes, collected curriculum and student work, and interviewed teachers and students to document and explain how racism was represented during the Civil Rights Movement. I found a consistent pattern of representing racism narrowly as individual prejudice across all three classes. Equating racism with individual prejudice was enabled by framing the unit around a Margaret Mead quotation regarding social change and the use of curricular materials that focused on the perspectives, choices, and actions on ordinary people in historical events. I conclude by arguing that equipping students to critically address racism in the United States today depends on enhancing the racial literacy of history teachers.